Resolving childhood trauma : a long-term study of abuse survivors - Cameron, Catherine (Sage Publications, 2000)
Through written questionnaires, extensive interviews and follow-up contacts, this insightful book analyses the impact of early trauma over subsequent years, examines the role of amnesia following trauma and monitors the progress toward recovery.